Indonesian Learner Cultural Characteristics and Perception toward Western Culture - ., Jalaluddin; Jazadi, Iwan (Universitas Hamzanwadi, 2020)
This paper argues that to have a successful learning of English in Indonesian schools, the consideration of culture should be at the forefront. That is, it is acknowledged that to learn English as a second or foreign language cannot be separated from the target language culture or the western culture. On the other hand, the perspective of English as global or international language allows the integration or use of students’ local cultural background into the teaching materials. To shed light on this critical issue, this study seeks to describe Indonesian learners’ characteristic cultural backgrounds and their perception toward western culture. Relying on a literature study and the first author’s experience and observation, the findings show that Indonesian learners share the culturally embedded characteristics of passivity, shyness, and lack of critical thinking, while perceiving western culture as negative, colonizing, dominating, and threatening. Therefore, it is concluded that English language teaching in Indonesia should integrate students’ local cultures and be prepared and implemented by highly skilled Indonesian teachers and practitioners who are abreast with ELT theories and development at the world level including those from the western world.